Comparative Effectiveness of Medication Therapy Management Eligibility Criteria Across Racial/Ethnic Groups. Issue 3 (23rd January 2019) - Spivey, Christina A.; Qiao, Yanru; Wang, Junling; Shih, Ya‐Chen Tina; Wan, Jim Y.; Dagogo‐Jack, Samuel; Cushman, William C.; Hines, Lisa E.; Chisholm‐Burns, Marie A.
Abstract : BACKGROUND/OBJECTIVES: Previous research indicates that eligibility criteria for medication therapy management (MTM) services in Medicare prescription drug (Part D) plans, defined under the Medicare Modernization Act (MMA), are associated with racial/ethnic disparities and ineffective in identifying individuals with medication utilization issues. Our study's objective was to determine the comparative effectiveness of MTM eligibility criteria under MMA and in the Affordable Care Act (ACA) in identifying patients with medication utilization issues across racial/ethnic groups. DESIGN: ACA and MMA MTM eligibility criteria were compared on proportions of eligible individuals among patients with medication utilization issues. Multinomial logistic regression was conducted to control for patient/community characteristics. Need‐based and demand‐based analyses were used to determine disparities due to need and demand for healthcare. Main/sensitivity analyses were conducted for the range of eligibility thresholds. SETTING: Medicare data (2012‐2013) linked to Area Health Resources Files. PARTICIPANTS: A total of 964 610 patients 65 years or older. MEASUREMENTS: Medication safety/adherence measures, developed primarily by the Pharmacy Quality Alliance, were used to determine medication utilization issues. RESULTS: Higher proportions of patients were eligible based on ACA than MMA MTM eligibility criteria. For example, in 2013, proportions based on ACA and MMA MTM eligibility criteria would be 99.7% and 26.2%, respectively, in the main analysis (p < .001); in the demand‐based main analysis, ACA criteria were associated with 13.6% and 9.8%, respectively, higher effectiveness than MMA criteria among non‐Hispanic blacks and Hispanics than non‐Hispanic whites. CONCLUSION: ACA MTM eligibility criteria are more effective than MMA criteria in identifying older patients needing MTM, particularly among minorities. J Am Geriatr Soc 67:581–587, 2019.